Pelatihan Pembuatan dan Pemasaran Digital Briket Limbah Sekam Di Desa Punggul, Sidoarjo - Oktafia, Linda; Kinanti, Isnatul Agil; Alisharsa, Muhammad Dafa; Irgie, Rafi; Istiqomah, Aisa Fadhilatul; Budiman, Arief (Universitas Negeri Surabaya, 2024)
This community service was carried out in RT 05 RW 02 Punggul Village, Gedangan District, Sidoarjo on November 25, 2023 for assistance in processing briquettes from biomass materials to be able to manage rice husk waste into more valuable briquettes and can become business products as well as marketing these briquette products digitally. The method used in the implementation of this activity is the preparation stage of the activity, the implementation of the activity, and the evaluation stage. The training activities for making briquettes from rice husk waste start from making dough, molding, drying, testing briquettes, and also digital marketing training, as well as creating social media accounts. The results of the implementation of this activity show the enthusiasm of Punggul villagers who can make briquettes from rice husk waste and have an understanding of marketing briquettes digitally through Instagram. The community is expected to be able to make briquettes independently by utilizing rice husk waste to become raw material for briquettes, and the community in Punggul Village has the skills to market briquettes by utilizing social media to do digital marketing. Keywords: Training, Briquettes, Husk, Marketing, Instagram